2019
DOI: 10.1155/2019/4304806
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Subsidy Policy for New Energy Automobile Industry in China Based on an Integrated Fuzzy-AHP-TOPSIS Methodology

Abstract: With the continuous tension of the international energy supply and the increasing appeal of the global environmental protection, the development of the new energy vehicle industry has attracted international attention. In order to support the development of new energy automobile production, China has frequently issued support policies. However, the problem of subsidy fraud has been exposed. erefore, in order to help the healthy development of China's new energy automobile industry and reduce the risk of subsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, it could not concurrently tackle the pairwise comparison involving triangular, general concave and concave [48]. Wang et al [49] used AHP to elicit a corresponding priority vector interpreting the preferred information from the decision-makers, based on the pairwise comparison values of a set of objects. Since pairwise comparison values are the judgments obtained from an appropriate semantic scale, in practice the decision-makers usually give some or all pair-to-pair comparison values with an uncertainty degree rather than precise ratings [50].…”
Section: The Evolution Of Fahp Theorymentioning
confidence: 99%
“…However, it could not concurrently tackle the pairwise comparison involving triangular, general concave and concave [48]. Wang et al [49] used AHP to elicit a corresponding priority vector interpreting the preferred information from the decision-makers, based on the pairwise comparison values of a set of objects. Since pairwise comparison values are the judgments obtained from an appropriate semantic scale, in practice the decision-makers usually give some or all pair-to-pair comparison values with an uncertainty degree rather than precise ratings [50].…”
Section: The Evolution Of Fahp Theorymentioning
confidence: 99%
“…Their findings indicated that the method used provided an operational evaluation decision-making system model. Furthermore, 15 representative energy enterprises in China were investigated and their performance was evaluated [43]. SF-AHP for F-TOPSIS was applied to rank the enterprises accordingly and they recommended differentiated subsidy policies for uncertainty evaluation to increase the credibility of the results.…”
Section: š‘€ Ģƒ= (š‘™ š‘š š‘¢)mentioning
confidence: 99%
“…The cumulative amount of subsidies exceeded 152.1 billion from 2010 to 2020. However, relying on national industrial policy support is not a long-term solution, especially with the emergence of "subsidy dependency" and "subsidy fraud" [ 1 ]. Since 2016, government subsidies have declined year by year.…”
Section: Introductionmentioning
confidence: 99%